2018
DOI: 10.1111/jsr.12656
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing in hypertensive disorders of pregnancy: a BMI‐matched study

Abstract: Sleep-disordered breathing is more common in hypertensive disorders during pregnancy; however, most studies have not adequately accounted for the potential confounding impact of obesity. This study evaluated the frequency of sleep-disordered breathing in women with gestational hypertension and pre-eclampsia compared with body mass index- and gestation-matched normotensive pregnant women. Women diagnosed with gestational hypertension or pre-eclampsia underwent polysomnography shortly after diagnosis. Normotensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…All subjects gave written informed consent to participate in the study. The data presented here is a secondary analysis of Wilson et al [10] which was a matched case-control study comparing the prevalence of SDB in women diagnosed with PE and GH to women with normotensive pregnancies.…”
Section: Study Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…All subjects gave written informed consent to participate in the study. The data presented here is a secondary analysis of Wilson et al [10] which was a matched case-control study comparing the prevalence of SDB in women diagnosed with PE and GH to women with normotensive pregnancies.…”
Section: Study Participantsmentioning
confidence: 99%
“…As per our initial study, [10] women diagnosed with GH or PE between 26 and 37 weeks gestation were considered as cases. Control participants were normotensive women with an uncomplicated pregnancy and were one-to-one matched by BMI to each of the hypertensive cases (within ±4kg/m 2 , measured at the first antenatal appointment).…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Accumulating evidence suggests this relationship may also exist in pregnancy with several studies reporting an association between SDB and gestational hypertensive disorders, [3,9,10] although obesity can act as a confounder to this relationship. [11] Hypertensive disorders of pregnancy (HDP), particularly preeclampsia, are associated with placental dysfunction resulting in impaired fetal growth and increased risks of acute compromise. [12][13][14][15] Whether co-existing SDB may increase these risks is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy, and particularly late gestation, has been associated with a relatively high prevalence of altered sleep patterns including restricted sleep duration, fragmented sleep, snoring, and especially OSA [55][56][57][58][59][60][61][62][63][64][65][66][67] . Experimental evidence in murine models has conclusively demonstrated that OSA can induce changes in insulin sensitivity and promote obesogenic behaviours as well as hypertension, i.e., correlates of pre-eclampsia [68][69][70][71][72][73][74] .…”
Section: Obstructive Sleep Apnoea During Pregnancy and Consequences Tmentioning
confidence: 99%